Entrepreneurial BMC Game: Developing High School Students' Numeracy Literacy Mastery - Efa Wahyu Prastyaningtyas; Widi Wulansari; Elis Irmayanti (Economics Education Department Universitas Negeri Semarang, 2025)
This study aims to test the effectiveness of the Entrepreneurial Business Model Canvas (BMC) Game in improving the numeracy literacy skills of high school students in red-ranked schools in Kediri City. Using a pseudo-experimental method with a one-group pre-test-post-test design on a small-scale trial (20 students of Sultan Agung High School) and a post-test-only design with a non-equivalent group on a large-scale trial (39 students of Al Anwar High School), the research applied a game that integrates entrepreneurial concepts with numeracy literacy. Data analysis using Paired t-test for small scale and independent t-test for large scale showed significant improvement in students' numeracy and literacy skills (p<0.05). On a small scale, the average score increased from 77.10 to 79.25, while on a large scale, the experimental group achieved an average of 79.38 compared to 77.00 for the control group. The Entrepreneurial BMC Game is proven effective in helping students develop their numeracy-based financial data analysis, business projection, and decision-making skills through collaborative and contextual learning. It offers an interesting and applicable alternative numeracy learning solution. Pedagogically, the game fosters active student engagement and enhances higher-order thinking by linking abstract numeracy concepts with real-world entrepreneurial contexts.